Growth enhancement support scheme (GESS) and farmers' fertilizer use in rural Nigeria - Joseph I. Uduji; Elda N. Okolo-Obasi; Simplice Asongu (African Governance and Development Institute (AGDI), 2019)
Fertilizer use in Nigeria is estimated at 13 kg/ha, which is far below the 200 kg/ha recommended by the Food and Agricultural Organization (FAO). The objective of this investigation was to identify the determinant factors of farmers' participation in the Nigeria's growth enhancement support scheme (GESS). In addition, we determined the impact of the GESS on fertilizer use in rural areas. One thousand, two hundred rural farmers were sampled across the six geopolitical zones of Nigeria. Results from the use of recursive bivariate probit model indicated that GESS significantly impacted on the access and usage of fertilizer among the rural farmers; and that contact with extension agents, ownership of mobile phones, power for charging phone batteries, value output, mobile network coverage, ability to read and write were positive determinants of rural farmers participation in the GESS; whereas increased distance to registration and collection centers, and cultural constraints to married women reduced farmers' tendency to participate in the GESS. The findings suggest that farmers' participation in the GESS is a critical factor for raising fertilizer use in Nigeria. This implies that food security in sub-Saharan Africa can be achieved by increasing the participation of rural farmers in the growth enhancement support scheme.
Keywords: O13; Q1; N27; 330; Growth Enhancement Support Scheme; Fertilizer Use; Rural Farmers; Recursive Bivariate Probit Model; Nigeria